Reader - Bernhard Schlink; Janeway Carol Brown Tr (London Phoenix)
An exceptionally powerful novel exploring the themes of betrayal, guilt and memory against the background of the Holocaust. An international bestseller.For 15-year-old Michael Berg, a chance meeting with an older woman leads to far more than he ever imagined. The woman in question is Hanna, and before long they embark on a passionate, clandestine love affair which leaves Michael both euphoric and confused. For Hanna is not all she seems. Years later, as a law student observing a trial in Germany, Michael is shocked to realize that the person in the dock is Hanna. The woman he had loved is a criminal. Much about her behaviour during the trial does not make sense. But then suddenly, and terribly, it does - Hanna is not only obliged to answer for a horrible crime, she is also desperately concealing an even deeper secret.'A tender, horrifying novel that shows blazingly well how the Holocaust should be dealt with in fiction. A thriller, a love story and a deeply moving examination of a German conscience' INDEPENDENT
Keywords: German Fiction in English; English Novel